2002
DOI: 10.1007/s00223-001-2068-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Omeprazole Treatment Does Not Influence Biochemical Parameters of Bone Turnover in Children

Abstract: Gastric proton pump inhibitors are widely used in the treatment of dyspeptic problems and for the eradication of H. pylori infection. Data are not available on whether omeprazole, a representative of proton pump inhibitors, influences the function of osteoclastic H+-pump in children. We studied the impact of short-term omeprazole administration on the biochemical parameters of bone turnover in pediatric patients. Urinary calcium excretion, serum total alkaline phosphatase activity, collagen type 1 crosslinked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 0 publications
2
24
0
1
Order By: Relevance
“…Kocsis et al 53 did not find different biochemical parameters of bone turnover in pediatric patients after omeprazole administration, which is in line with our results. On the other hand, a favorable bone response of omeprazole administration was seen in the study of Mizunashi et al, 22 who showed a suppression in bone resorption in adult patients treated with gastric PPIs.…”
supporting
confidence: 83%
“…Kocsis et al 53 did not find different biochemical parameters of bone turnover in pediatric patients after omeprazole administration, which is in line with our results. On the other hand, a favorable bone response of omeprazole administration was seen in the study of Mizunashi et al, 22 who showed a suppression in bone resorption in adult patients treated with gastric PPIs.…”
supporting
confidence: 83%
“…Omeprazole is a weak inhibitor of proton transport within osteoclasts [ 18 ]. Although a biochemical study in children did not demonstrate increased bone turnover with shortterm omeprazole use [ 19 ], a comparable study in adults found lower rates of urinary calcium and hydroxyproline excretion with omeprazole compared with H 2 RA use [ 20 ]. The authors hypothesized that omeprazole may suppress osteoclast activity, thereby decreasing bone resorption and possibly having a role in the management of metabolic bone diseases.…”
Section: Calcium Malabsorption and Bone Metabolismmentioning
confidence: 95%
“…Furthermore, the effects of PPIs on skeletal metabolism have not been well studied and the studies available give differing results. In some studies markers of bone turnover have been altered by PPI treatment in humans suggesting PPIs alter bone resorption, whereas in other studies no affect on bone turnover was seen [48,49,66,67]. …”
Section: Long-term Use Of Ppis and Effects On Calcium Absorption/mentioning
confidence: 99%